2023
DOI: 10.1155/2023/6392669
|View full text |Cite
|
Sign up to set email alerts
|

Design and Management of Micro-Teaching Mode of Education in Colleges Driven by Big Data

Abstract: Big data has become a new driving force for national innovation and entrepreneurship. Although colleges and universities, which are responsible for cultivating high-quality entrepreneurship and innovation talents, have achieved certain results, there are still many problems in practice, which need to be driven by big data. Big data and the practice of innovation and entrepreneurship education in colleges and universities have certain inherent commonality. The integration of big data into the practice of innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Jin) [11] These findings were published in the journal Teaching and Teacher Education. In addition, research on intrinsic motivation has shown that instructors who find their work to be fun and personally fulfilling are more likely to provide help to their pupils, and this in turn has a positive effect on the academic performance of those pupils.…”
mentioning
confidence: 84%
“…Jin) [11] These findings were published in the journal Teaching and Teacher Education. In addition, research on intrinsic motivation has shown that instructors who find their work to be fun and personally fulfilling are more likely to provide help to their pupils, and this in turn has a positive effect on the academic performance of those pupils.…”
mentioning
confidence: 84%